Pembelajaran Pendidikan Agama Islam Secara Daring Dan Permasalahannya - Latipah, Eva; Awalliyatunnisa, Dinda (LPPM Sekolah Tinggi Agama Islam Al Azhar, 2021)
Online learning of islamic religion education and the problems. PAI learning is learning that emphasizes aspects of attitude. Of course this raises its own problems considering that attitude learning is learning that demands the appreciation of the values ​​of Islamic Education. This study aims to examine how online Islamic education learning is during a pandemic? What problems do teachers and students face during online Islamic Education learning? This research is a field research with a qualitative approach. Data collection used interviews with students and teachers by telephone and in person by strictly applying health protocols. The subjects of this study were students and teachers who were directly involved in online Islamic Education learning.The results showed: 1) online PAI learning adapts to government policies ranging from learning planning, simplified learning materials, learning media using google classroom and the WA group, learning methods often using lectures and assignments, assessment using assignments (work chores). 2) The problems of online Islamic education learning faced by teachers are: teachers find it difficult to teach because students are passive, teachers feel tired and bored, the available learning media do not have ideal facilities, cannot control the learning process comprehensively. Online learning problems faced by students are: limited cellphone storage capacity, signal and quota constraints, and lack of motivation (learning feels bland and not serious because it cannot see or listen to the teacher's explanation directly).